MODIFIKASI MESIN PENGEPRES SARI BREM SISTEM HIDROLIK UNTUK MENINGKATKAN KUALITAS DAN KUANTITAS PRODUKSI UKM BREM MADIUN - F., Fatkhurrohman; M., Muji; Wijendra, Sutra Angga (Program Kreativitas Mahasiswa - Teknologi, 2013)
SME partners making brem business activity is managed by Mrs. Sukiati at Kaliabu village located at Madiun. Based on observations and interviews conducted by the team this PKM SME partners that the data obtained in the pressing process to take the juice of raw material is done manually. White glutinous pressing process (raw material brem) was performed using a less efficient equipment (12kg/process limited capacity). Besides, the pressing tool is not hygienic (wood and bamboo). Purpose of this activity is to improve productivity of SMEs with indicators: (1) accelerate the process of pressing sticky tape material originally brem 150 kg/day to 300 kg/day; (2) improve the quality of production, due to the changing methods performed manually are now becoming more hygienic. Expected outcomes of the event realization sticky tape pressing machine of the hydraulic system as a raw material brem. The result of activities are: (1) the realization of sticky tape pressing machine hydraulic system, (2) the process of pressing sticky tape material brem be over 2 times faster than the original 150 kg/day to 300 kg/day, (3) qualities brem production increases, because the pressing tool originally done using wood and bamboo are now becoming more hygienic done by machine.